Digital Economy in Business & Economics: A Systematic Literature Review and Bibliometric Analysis - Bitzenis, Aristidis; Koutsoupias, Nikos (Proceedings of the International Conference on International Business (ICIB) 2023–2024, 2025)
This study reviews the evolving research literature of the Digital Economy in Business & Economics (DEBE) through a bibliometric analysis. By exploring 1,273 papers from the Scopus database (2013–2022), we uncover trends and progress in the field. Our findings show substantial growth in DEBE-related research between 2017 and 2022, with contributions from around 3,300 researchers across 80 countries. We highlight major journals, prominent countries, and key research themes, providing valuable insights on areas that deserve further exploration. This study is particularly useful for academics and professionals looking to stay informed, collaborate, or shape future research in Business, Economics, and Digital Transformation. Beyond mapping the existing literature, our work aims to inspire further studies and meaningful collaborations in this rapidly growing field.